Contraception: Influence on vaginal microbiota and identification of vaginal lactobacilli using MALDI-TOF MS and 16S rDNA sequencing - Fosch, Sonia E. (2018)
The vaginal microbiome is influenced by a wide variety of factors, including contraceptive methods. To evaluate the effect of contraceptive methods on vaginal microbiota and to compare MALDI-TOF MS and 16S rDNA sequencing for lactobacilli identification. Patients and Methods: One hundred and one (101) women consulting for birth control were included in a prospective study. Their vaginal content was sampled and analyzed once before they started using the contraceptive method of their choice, and twice after the initiation of contraception, at three months (94/101 women attended) and at six months (89/101 women attended). The relative frequencies of yeasts and trichomonas were analyzed. MALDI-TOF MS and 16S rDNA sequence analysis were applied for the identification of lactobacilli in their vaginal microbiota. The following contraceptive methods were assessed: Combined Oral Contraceptive Pill (COCP), Condom (CON) and The Rhythm Method (RHYT). McNemar's statistical test was applied. A statistically significant association between COCP and normal microbiota was observed after three months (p< 0.01) and after six months (p< 0.0001), when the vaginal microbiota was modified. At six months, inflammatory reaction was detected in 3/7 women in the CON group, while 6/7 patients using RHYT showed the same state. Yeast colonization increased with the COCP. Identification of lactobacilli by MALDI-TOF MS analysis compared to 16S rDNA sequencing yielded 92.9% concordant results. Lactobacillus gasseri and L. crispatus were the predominant species. The pattern of vaginal states was significantly modified. Hormone administration apparently corrected the alterations and retained a normal vaginal state. MALDI-TOF MS has the potential of being an accurate tool for the identification of vaginal lactobacilli species L. murinus was for the first time isolated from the vagina.